The performance enhancement attitude scale (PEAS) reached 'adulthood': Lessons and recommendations from a systematic review and meta-analysis. (September 2021) - Folkerts, Dirk; Loh, Roland; Petróczi, Andrea; Brueckner, Sebastian
Abstract: Doping is an omnipresent issue in both professional and amateur sports. Advances in social science research, including studies on doping attitude, have played a pivotal role in developing an understanding that prohibition and testing alone do not deter athletes from doping. Research on doping attitude has relied heavily on the Performance Enhancement Attitude Scale (PEAS). Yet, to date, no systematic review and meta-analysis of the PEAS have been conducted. Thus, the purpose of this study is, for the first time, to cumulate evidence for the psychometric properties of PEAS; specifically to conduct a qualitative synthesis and perform a meta-analysis to analyze the available results and findings for internal consistency reliability, gender differences and user/non-user differences in doping attitude assessed by the PEAS. PRISMA protocol was employed for data identification and selection. Included articles were assessed for data quality and biases. Meta-analysis with random effects models was used to determine overall internal consistency reliability (Cronbach's alpha) and descriptive statistics (Mean, SD) for a subset of studies using the full 17-item PEAS. Eighty-two studies were eligible for qualitative synthesis, and data from a subsample of 44 studies were meta-analyzed. The quantitative analyses yield an overall PEAS score of 39.18 (2.30 on a 6-point scale) and good internal consistency reliability (Cronbach's α = 0.81 [95%CI 0.80, 0.83]). Males and admitted doping users scored higher on PEAS then females and non-users, but still within the 'negative' spectrum. Medium to strong correlations were recorded with moral disengagement (r = 0.42–0.75). Overall, negative doping attitude characterized the athlete population, regardless of gender or involvement in doping. The latter, coupled with sole reliance on self-reports for doping, questions the validity of PEAS as proxy for indexing doping behavior. Future research will benefit from a standardized short version of PEAS. The consistent 'negative' range observed in PEAS scores, even among admitted dopers, suggests a potential moral conviction angle, which may limit the scale's utility as a global attitude measure and calls for further research whether re-calibration of the scale as a measure of moral doping attitude is warranted. Advances in doping behavior research calls for a more nuanced understanding of the role of attitudes toward doping and clean sport behavior; new and more specific attitude measures toward doping that separate moral and functional aspects effectively, along with a psychometrically sound instrument for adolescents. Highlights: Performance Enhancement Attitude Scale (PEAS) has been the main assessment tool for doping attitude. For the first time, meta-analysis was extended to internal consistency reliability. PEAS is reliable measure of moral doping attitude for adults. Evidence suggests that PEAS is not a suitable proxy for indexing doping behavior. For comparability, a standardized short version of PEAS is needed.